NURSING DIAGNOSIS APPLIED TO PATIENTS WITH DECOMPENSATED HEART FAILURE - Paulo Cesar da Costa Galvão; Eduardo Tavares Gomes; Thaisa Remigio Figueirêdo; Simone Maria Muniz da Silva Bezerra (Universidade Federal do Paraná, 2016)
The present study aimed to identify the priority nursing diagnoses for patients with decompensated heart failure. Quantitative study conducted in a cardiac emergency service of a university of Pernambuco, between October 2014 and February 2015. The study sample was composed of 62 patients admitted for the treatment of acute decompensated heart failure, emergency inpatients and patients from any functional class. The main nursing diagnoses were Decreased Cardiac Output (87.3%), Activity Intolerance (79.4%) and Ineffective Breathing Pattern (38.1%). The signs and symptoms of decompensation caused by systemic or pulmonary congestion provided the basis for the recognition of defining characteristics that made it possible to formulate priority nursing diagnoses for these patients.